Belief or disbelief in feedback influences the detection efficiency of the feedback concealed information test - Cheng, Jiayu; Sai, Yanyan; Zheng, Jinbin; Olson, Joseph M.; Sai, Liyang (Frontiers in Psychology, 2022)
The feedback concealed information test (fCIT) is a new variant of the CIT that added feedback about participants’ concealing performances in the classical CIT. The advantage of the fCIT is that the resulting feedback related event-related potentials (ERPs) can be used to detect concealed information. However, the detection efficiency of feedback-based ERPs varies across studies. The present experiment examined whether the extent participants believed the feedback influenced their detection efficiency. Specifically, participants did a mock crime and were then tested in a fCIT. Following the fCIT, participants were asked to report how much they believed the feedback was accurate. Results showed that there were no significant correlations between the amplitude of the feedback related negativity (FRN), feedback P300 and participants’ self-report at the group level. However, individual analyses showed that the detection efficiency of both the FRN and feedback P300 were influenced by participants’ belief about the presented feedback. The detection efficiency of the FRN and the feedback P300 was higher among participants who believed the feedback. These findings suggest that the fCIT is dependent to some extent on the participants' level of belief in the feedback.